Psychoeducation on Qur’an-Based Child Care for Underage Millennial Engaged Couples - Miftahul Jannah; Salwa Dhevira Rahmayani (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
Quranic-based counseling is an integrative therapeutic approach that blends Islamic spiritual teachings with psychological support to address various mental, emotional, and behavioral issues. This study explores the conceptual framework, structure, and outcomes of the A–R Model Quranic Counseling, which is designed to assist clients dealing with trauma, illness, anxiety, deviant behavior, and spiritual emptiness. Using a psychoeducational and psychotherapeutic approach, the model operates in five structured phases: acceptance, initial contact, encounter, summary, and follow-up. The counselor functions not only as a spiritual guide but also as a support system for clients and their families, taking into account individual values, religious beliefs, and sociocultural backgrounds. Results from multiple case applications show significant positive changes in clients’ behavior, emotional regulation, spiritual awareness, and decision-making. Clients reported feeling calmer, more focused in worship, more responsible in behavior, and more optimistic in facing life’s challenges. These findings highlight the potential of Quranic counseling as a holistic and culturally relevant model for enhancing psychological and spiritual well-being, especially among Muslim communities.